2011
DOI: 10.1002/prot.23083
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of small molecule inhibitors of the Bcl‐2 family

Abstract: We carried out docking and molecular dynamics simulations on ABT-737 and obatoclax, which are inhibitors of the Bcl-2 family of proteins. We modeled the binding mode of ABT-737 with Bcl-x(L) , Bcl-2, and Mcl-1 and examined their dynamical behavior. We found that the binding of the chlorobiphenyl end of ABT-737 was quite stable across all three proteins. However, the phenylpiperazine linker group was dramatically more mobile in Mcl-1 compared to either Bcl-x(L) or Bcl-2. The S-phenyl group at the p4 binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 57 publications
(86 reference statements)
1
21
0
Order By: Relevance
“…One such agent is obatoclax (OBX), a synthetic indolylprodigiosin derivative that was shown to bind to Bcl-2, Bcl-xL, Bcl-w and Mcl-1 [19][20][21]. Preclinical studies have shown that OBX is effective as a single agent against a broad range of cancer cell lines and xenografts [22] and that it synergizes with a number of cytotoxic and targeted anticancer agents [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 98%
“…One such agent is obatoclax (OBX), a synthetic indolylprodigiosin derivative that was shown to bind to Bcl-2, Bcl-xL, Bcl-w and Mcl-1 [19][20][21]. Preclinical studies have shown that OBX is effective as a single agent against a broad range of cancer cell lines and xenografts [22] and that it synergizes with a number of cytotoxic and targeted anticancer agents [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 98%
“…The structures of antiapoptotic protein (Bcl-2, Bcl-xL, and Mcl-1) consist primarily of two central hydrophobic helices surrounded by amphipathic helices (Petros, Olejniczak, & Fesik, 2004;Day et al, 2005). The binding groove is formed mainly by the α2, α 3, α 4, and α 5 helices (Acoca, Cui, Shore, & Purisima, 2011) (Figure 1). Ku et al (2011) found that the 31-mer Bax peptide (residues 52-82) and the 36-mer Bax peptide (residues 49-84) bind Bcl-2 nearly with equal potency.…”
Section: Introductionmentioning
confidence: 98%
“…All the previous studies regarding the inhibition of Bcl-2 were mainly targeted to the Bax-unbound form of Bcl-2 (Acoca et al, 2011;Mohammadi et al, 2014;Saxena et al, 2013) in our knowledge. It is well defined that the interaction of bcl-2 and bax is mainly dependent on few residues of both proteins.…”
Section: Introductionmentioning
confidence: 99%
“…22 Additionally, a broader p4 pocket in Mcl-1 than that in Bcl-2 has been revealed by a molecular dynamics study. 15 These studies suggested that the p4 pocket has less contribution to Mcl-1 binding. In the present study, however, we found binding affinities to Mcl-1 were progressively improved accompanied with increased p4 occupation.…”
Section: Comparing the Different Contribution Of P4 To Binding Affinimentioning
confidence: 99%
“…Previous studies have reported that Bcl-2 and Mcl-1 show differences in the structure of their p4 pockets. 15 When we tried to occupy the p4, an optimization path should be carefully designed to resolve differences of the p4 between Bcl-2 and Mcl-1 without losing either one. At the outset, we aimed to maintain the binding mode with R263 in Mcl-1 and R146 in Bcl-2 constant since the key hydrogen bound was formed in this region.…”
Section: Rationalementioning
confidence: 99%